#descontent@mento: o que comunicam os protestos brasileiros de 2013 - Carrasco, Vinícius (2015)
Over the past few years, social movements have emerged in the network around the globe by combining the use of computer-mediated communication as an articulator form of events and demonstrations, the occupation of cities and public space. The Brazil could also experience a particular experience in this regard from the June 2013 demonstrations, a priori, claiming the rate reduction and improvement of public transport. This paper aims, through a theoretical approach and observation of contemporary situate such protests within the communication perspective, systematize and point out the characteristics of these movements as spatialities of communication and networking activism, analyze such manifestations in your communication sphere, this process involving communicative action and production of meaning with the appropriation of new media and digital social networks by contemporary social movements. It is intended to study the communicating these prostests, infer which identifies and social representations are constructed with such messages are considered symbolic productions and analyze how movements for collective action as the Free Pass Movement São Paulo (MPL-SP) an its organizers, appropriate the communication potential of digital social networks as a way enginner social mobilization, promoting their causes and lead to political discussions streets. For this purpose, use is made also analyzed the content of the messages between the movement and the users of their official Facebook page. It is expected, therefore, contribute to the discussion about the unique role of communication in contemporary society and how activism networking relates to the exercise of citizenship, the discussion of issues of public interest and the political and social participation, address the legacy of these events while generating of what I call culture of protests, a symbolic dimension that translates into collective action network as reactive experience...